2016
DOI: 10.1111/jvp.12380
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/pharmacodynamic evaluation of grapiprant in a carrageenan‐induced inflammatory pain model in the rabbit

Abstract: Grapiprant is the novel selective EP4 receptor inhibitor recently issued on the veterinary market for dogs affected by osteoarthritis. The aim of this study was twofold: to evaluate the pharmacokinetics and the pharmacodynamics of grapiprant in the induced inflammatory pain model in the rabbit after a single IV injection of 2 mg/kg; to compare the thermal antinociception effect after 2 mg/kg IV grapiprant, with that generated by 0.5 mg/kg meloxicam SC injected. Rabbits (n = 12) were randomly assigned to two cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…However, care with these data is needed because it is recognized that there may be some discrepancy between plasma concentration and actual effect at the receptor level (Toutain & Lees, ). Indeed a recent study found a protracted effect of grapiprant in the rabbit suggesting the generation of an active metabolite or a slow dissociation from the receptor (De Vito et al., ). Notably, the pharmacokinetic–pharmacodynamic hysteresis loop could be different in diverse species, and parameters, such as the onset time and time over the MEC, should be verified with ad hoc pharmacokinetic–pharmacodynamic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, care with these data is needed because it is recognized that there may be some discrepancy between plasma concentration and actual effect at the receptor level (Toutain & Lees, ). Indeed a recent study found a protracted effect of grapiprant in the rabbit suggesting the generation of an active metabolite or a slow dissociation from the receptor (De Vito et al., ). Notably, the pharmacokinetic–pharmacodynamic hysteresis loop could be different in diverse species, and parameters, such as the onset time and time over the MEC, should be verified with ad hoc pharmacokinetic–pharmacodynamic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Grapiprant is identified as a competitive antagonist of prostanoid EP 4 receptors with similar potency in humans, rats (Nakao et al., ) and in dogs (Nagahisa & Okumura, ). A randomized multisite clinical study has shown grapiprant as being effective for alleviation of pain in dogs with osteoarthritis, and a recent study has shown its effectiveness (comparable to meloxicam) in a carrageenan inflammatory model in the rabbit (De Vito et al., ). A recent study (Rausch‐Derra & Rhodes, ) reported very few toxicokinetic parameters and no concentration versus time profile curves in cats.…”
Section: Introductionmentioning
confidence: 99%
“…Carrageenan (CAR)-induced inflammation is a recognized and highly reproducible model of acute inflammation and inflammatory pain [ 39 , 40 ]. Briefly, rats were anesthetized with 5.0% isoflurane in 100% O2 (Baxter International, Rome, Italy) and received a subplantar injection of carrageenan (CAR, 0.1 ml/rat of a 1% suspension in saline) (Sigma-Aldrich, Milan, Italy) with a 27-gauge needle into the right hind paw, as previously described [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of analytical methods for the quantification of grapiprant in different biological matrices have been published (Baralla et al, 2018 ; Cox et al, 2020 ; De Vito et al, 2016 , 2017 ; Heit et al, 2018 ; Knych et al, 2018 ; Łebkowska‐Wieruszewska et al, 2017 ; Nagahisa & Okumura, 2017 ). The devices used for the quantification of grapiprant are HPLC and LC‐MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetics of grapiprant after 2 mg/kg IV administration were described (De Vito et al, 2017 ). Grapiprant plasma concentrations were detectable up to the 10‐h time point (concentration range 17–7495 ng/ml).…”
Section: Pharmacokineticsmentioning
confidence: 99%